Cost-utility and budget impact analyses of cervical cancer screening using self-collected samples for HPV DNA testing in Thailand - Chayanis Kositamongkol; Sukrit Kanchanasurakit; Euarat Mepramoon; Pattarawalai Talungchit; Pattama Chaopotong; Kirati Kengkla; Thanet Chaisathaphol; Surasak Saokaew; Pochamana Phisalprapa (BMC, 2023)
Abstract Introduction Cervical cancer ranks as the third most prevalent cancer among women in Thailand. However, the effectiveness of cervical cancer screening programs is limited by several factors that impede the screening rate. The utilization of self-collected samples for screening purposes has the potential to alleviate barriers to screening in Thai women. This study assessed the cost-utility and budget impact of implementing cervical cancer screening using self-collected samples for human papillomavirus (HPV) deoxyribonucleic acid (DNA) testing in Thailand. Materials and methods We employed a decision tree integrated with a Markov model to estimate the lifetime costs and health benefits associated with the cervical cancer screening program for women aged 25-65. The analysis was conducted from a societal perspective. Four screening policy options were compared: (1) additional self-collected samples for HPV DNA testing, (2) clinician-collected samples for HPV DNA testing only, (3) clinician-collected samples for cytology test (i.e., status quo), and (4) no screening. The model inputs were based on unvaccinated women. The screening strategies and management in those with positive results were assumed followed to the Thai clinical practice guideline. Costs were reported in 2022 Thai baht. Sensitivity analyses were conducted. The ten-year budget impacts of the additional self-collected samples for HPV DNA testing were calculated from a payer perspective. Results All screening policies were cost-saving compared to no screening. When comparing the additional self-collected samples for HPV DNA testing with the clinician-collected samples policy, it emerged as the dominant strategy. The incremental benefit in cervical cancer prevention achieved by incorporating self-collected samples for screening was observed at any additional screening rate that could be achieved through their use. Sensitivity analyses yielded consistently favorable results for the screening policies. The average annual budget impact of the additional self-collected samples for screening policy amounted to 681 million Thai baht. This budget allocation could facilitate cervical cancer screening for over 10 million women. Conclusions An addition of self-collected samples for HPV DNA testing into the cervical cancer screening program is cost-saving. The benefits of this screening policy outweigh the associated incremental costs. Policymakers should consider this evidence during the policy optimization process.